The Prevalence and Associated Factors of Depression in ESRD on Hemodialysis in Phra Nakhon Si Ayutthaya Hospital - ปลูกรักษ์, สุภิศา (Journal of Preventive Medicine Association of Thailand, 2018)
Depression is a common psychiatric disorder in patients affected by chronic kidney disease. If it is early diagnosed, the mortality rate and the disability could be reduced and the quality of life could be improved. This study aimed to investigate prevalence and associated factors of depression among end stage renal disease patient on hemodialysis in Phra Nakhon Si Ayutthaya Hospital, Phra Nakhon Si Ayutthaya Province. A cross-sectional study was conducted in 91 end stage renal disease patients, who visited hemodialysis unit in November-December 2017. General demographic data questionnaire and the Patient Health uestionnaire Thai-version (PHQ-9 Thai-version) were used to identify depression. Descriptive statistics were employed to describe sample characteristics and prevalence. Multiple logistic regression was performed for testing the associations between depression and related factors. The p<0.05 was considered as a statistical significance. The results showed that 17.6% had depression (PHQ-9 ≥9). There were 2 factors that had statistically significant association with depression: dialysis duration for less than 4 years (OR=3.91 95%CI 1.23-12.45) and family conflict (OR=6.36 95%CI 1.58-25.63). Depression in end stage renal disease patients still has problems and complications. It suggests encouraging the patient to psychological adjustment evolves towards an acceptance of the disease and a significant reduction in the psychological symptoms of depression. In addition, family counseling and referral to psychiatrist should be provided for treatment.